2020
DOI: 10.1186/s41016-020-00190-5
|View full text |Cite
|
Sign up to set email alerts
|

Urinary biomarker discovery in gliomas using mass spectrometry-based clinical proteomics

Abstract: Background: Gliomas are the most common primary malignant brain tumors and have a poor prognosis. Early detection of gliomas is crucial to improve patient outcomes. Urine accumulates systematic body changes and thus serves as an excellent early biomarker source. Methods: At the biomarker discovery phase, we performed a self-controlled proteomics analysis by comparing urine samples collected from five glioma patients at the time of tumor diagnosis and after surgical removal of the tumor. At the biomarker valida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…Previous studies have shown that urine could enrichment changes in all parts of body and is a highly sensitive matrix indicative of pathological changes in the body (Wu and Gao, 2015). Thus, urine presents an early biomarker source with the potential to reflect small, early pathological changes signifying the onset of diseases such as cancer (Wu et al, 2020). Evaluation of the performance of our novel classifier supports its potential in non-invasive early stage diagnosis.…”
Section: Discussionmentioning
confidence: 53%
“…Previous studies have shown that urine could enrichment changes in all parts of body and is a highly sensitive matrix indicative of pathological changes in the body (Wu and Gao, 2015). Thus, urine presents an early biomarker source with the potential to reflect small, early pathological changes signifying the onset of diseases such as cancer (Wu et al, 2020). Evaluation of the performance of our novel classifier supports its potential in non-invasive early stage diagnosis.…”
Section: Discussionmentioning
confidence: 53%
“…The following filter was used in this study, 1% false-positive rate at protein level and each protein with ≥1 unique peptides and protein areas were used for protein quantification. 11 , 12 After filtering the results by above filter, proteins were exported for proteomic analysis workflow described here.…”
Section: Methodsmentioning
confidence: 99%
“…Informative urinary biomarkers of glioma have been analyzed [68][69][70]. A biomarker panel consisting of Alpha-1-antichymotrypsin (AACT), Thrombospondin-4, Malate dehydrogenase mitochondrial, Calreticulin, Galectin-1 (LEG1), and Alpha-2-HS-glycoprotein (AHSG) showed the best glioma diagnosis accuracy, with an area under the curve value of 0.96, as well as the sensitivity and specificity of 0.9 and 0.92, respectively [68]. AACT, LEG1, and AHSG are also potential cerebrospinal fluid or blood biomarkers of gliomas.…”
Section: Proteinsmentioning
confidence: 99%